Peace Journalism and the Kurdish Question: A Frame Analysis of the Peace Process in the Turkish Press - Atay, Ayça Demet (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2016)
ABSTRACT: Peace journalism, that aims to contribute to peaceful transformation of conflicts, emphasizes the free will of journalists on what to report and how to report it. However, what if ―peace‖ becomes the official policy of the state, and the state imposes pressure on the media to act in line? Can the resulting form of journalism be still considered as peace journalism if it is ordered to support peace? This study assesses these questions within the context of the peace negotiations between the Kurdistan Workers‘ Party (Partiya Karkerên Kurdistan- PKK) and the Turkish state. A quantitative frame analysis of the news coverage of the peace process in eleven Turkish newspapers, Cumhuriyet, Habertürk, Hürriyet, Milliyet, Sabah, Sözcü, Taraf, Türkiye, Yeni Şafak, Yeniçağ and Zaman, is conducted in an effort to examine how the so-called ―resolution process‖ was constructed in the mainstream Turkish press in the time period of 2013. The results are compared with the qualitative frame analyses of two cases: PKK leader Abdullah Öcalan‘s Newroz message where he called the armed organization to withdraw across the border on 21 March 2013 and the press conference at the PKK base in Mount Qandil on 25 April 2013, where the PKK announced that they will withdraw. Front pages of the selected newspapers on the consecutive days of these two key events are analysed. The results show that the Turkish press, with the exception of nationalist dailies, supported the peace process in the selected time period. Considering the state-media relations in the country, this study names this form of journalism as ―state-imposed peace journalism. Keywords: Peace journalism, Turkey, peace process, state-media relations, Kurdish question, frame analysis.

ÖZ: ÇatıĢmaların barıĢçıl yollardan dönüĢtürülmesine katkıda bulunmayı hedefleyen barıĢ gazeteciliği, neyin nasıl haberleĢtirileceği konusunda gazetecilerin özgür iradesine vurgu yapar. Ancak ya ―barıĢ‖ devletin resmi politikası haline gelirse ve devlet medyayı hizada tutmak için baskı uygularsa? Bu durumda ortaya çıkan gazetecilik, barıĢı desteklese bile barıĢ gazeteciliği olarak nitelendirilebilir mi? Bu çalıĢma, bu sorulara Kürdistan ĠĢçi Partisi (Partiya Karkerên Kurdistan- PKK) ile Türkiye devleti arasındaki barıĢ görüĢmeleri bağlamında yanıt aramaktadır. ―Çözüm süreci‖ olarak adlandırılan sürecin, ana akım Türk basınında 2013 yılı içinde nasıl inĢa edildiğini incelemek amacıyla on bir Türk gazetesini- Cumhuriyet, Habertürk, Hürriyet, Milliyet, Sabah, Sözcü, Taraf, Türkiye, Yeni Şafak, Yeniçağ ve Zaman- kapsayan nicel bir çerçeveleme analizi gerçekleĢtirilmiĢtir. Bu araĢtırmanın sonuçları iki vakanın – PKK lideri Abdullah Öcalan‘ın silahlı örgüte sınır dıĢına çıkmaları çağrısında bulunduğu 21 Mart 2013 tarihli Nevruz mesajı ve 25 Nisan 2013‘te PKK‘nın Kandil Dağı‘ndaki üssünde gerçekleĢtirilen örgütün çekileceğini açıkladığı basın toplantısı- temsilini içeren nitel çerçeveleme analizleri ile karĢılaĢtırılmıĢtır. Seçilen gazetelerin bu iki önemli olayın ertesi gününde yayımlanan baĢ sayfaları incelenmiĢtir. Sonuçlar göstermektedir ki milliyetçi gazeteler dıĢındaki Türk basını seçilen zaman döneminde barıĢ sürecini desteklemiĢtir. Ülkedeki devlet-medya iliĢkileri göz önünde bulundurulduğunda, bu çalıĢma bu gazetecilik biçimini ―devlet tarafından dayatılan barıĢ gazeteciliği‖ olarak adlandırmaktadır. Anahtar kelimeler: BarıĢ gazeteciliği, Türkiye, barıĢ süreci, devlet-medya iliĢkileri, Kürt sorunu, çerçeveleme analizi
Doctor of Philosophy in Communication and Media Studies. Thesis (Ph.D.)--Eastern Mediterranean University, Faculty of Communication, Dept. of Communication and Media Studies, 2016. Supervisor: Prof. Dr. Süleyman İrvan.
Keywords: Communication and Media Studies Department; Peace Journalism - Turkey; Social conflict - Press coverage; Mass media and peace; Peace journalism, Turkey, peace process, state-media relations, Kurdish question, frame analysis